Making globalization socially sustainable (Geneva, 2011)
"Globalization is widely seen as a powerful engine that has the potential to promote growth and development. For many years, however, concerns have also been raised about the effects of globalization on jobs and wages. This has led to questions about the social sustainability of globalization. Jointly published by the ILO and the WTO, with funding by the International Chamber of Commerce, this publication consists of contributions by leading academic experts who analyse the various channels through which globalization affects jobs and wages. Together, the nine chapters in this volume summarize state-of-the art knowledge on themes related to the social dimension of globalization. The volume, therefore, represents a step in the direction of a better understanding of the mechanisms through which globalization affects workers and of the measures that governments can take to give globalization a strong social dimension. It will be of value to all those who are interested in the debate on the social sustainability of globalization, including workers and employers, policy-makers, academics, and other trade and labour specialists. "